Iron-citrate can induce cell senescent phenotype in human fibroblasts in vitro - Matos, Liliana (2009)
After a number of replications, human diploid fibroblasts (HDFs) in culture lose the ability to divide, become insensitive to further proliferation and enter a state of replicative senescence (RS). Subcytotoxic doses of several stressful agents such as hydrogen peroxide, tertbutylhydroperoxide or ethanol, are able to cause stress-induced premature senescence (SIPS) in HDFs in vitro. Such senescent cells display many features of RS as growth arrest, senescence associated beta-galactosidase (SA beta-gal), cell enlargement and overexpression of several genes (e.g., p21, TGF beta-1,IGFBP3). During ageing, iron accumulates in several tissues in vivo, and also in senescent HDFs in vitro. Due to its redox-active properties, it promotes hydroxyl radical production (Fenton reaction) and eventually leads to cell injury. Free radical reactions are known to cause the accumulation of intracellular damage resulting in ageing. Iron may thus be able to cause SIPS. The main objective of the present study was to investigate whether the exposure of HDFs to a subcytotoxic concentration of iron is able to cause SIPS.